Applying the scientific method when assessing the influence of migratory birds on the dispersal of H5N1 - Flint, Paul L (BioMed Central, 2007)
BACKGROUND: The role of wild birds in the dispersal of highly pathogenic avian influenza virus H5N1 continues to be the subject of considerable debate. However, some researchers functionally examining the same question are applying opposing null hypotheses when examining this issue. DISCUSSION: I describe the correct method for establishing a null hypothesis under the scientific method. I suggest that the correct null hypothesis is that migratory birds can disperse this virus during migration and encourage researchers to design studies to falsify this null. Finally, I provide several examples where statements made during this debate, while strictly true, are not generally informative or are speculative. SUMMARY: By adhering to the scientific method, definitive answers regarding the role of wild birds in the dispersal of highly pathogenic viruses will be reached more effectively.